Mechanical behaviour of pitting corrosion of flexural and shear reinforcement and its effect on structural reliability of corroding RC beams - Stewart, Mark G. (Structural safety, 2009)
A spatial time-dependent reliability model is developed for a RC beam subject to corrosion-induced pitting corrosion, for shear and flexural limit states. The analysis considers the spatial and time-dependent variability of pitting corrosion, structural resistance and load effects. The amount of corrosion loss can significantly affect the mechanical behaviour of reinforcement, namely low corrosion loss can result in ductile yielding, whereas a higher corrosion loss can result in brittle fracture. The progression from ductile to brittle behaviour is spatially and time-dependent. To estimate how such phenomena affects structural reliability the structural resistance of reinforcement is modelled as either (i) perfectly ductile parallel system or (ii) perfectly brittle parallel system. It was found that the probability of failure assuming brittle reinforcement behaviour is up to 450% higher than assuming ductile behaviour.